DILEMMAS IN THE DIAGNOSIS OF DORSALLY SEQUESTERED DISC IN THE THORACIC SPINE AS A RARE CONDITION - Antuleska Becheska, Gordana; Bundovska Kocev, Smiljana; Stojovska jovanovska, Elizabeta (SHMSHM / AAMD, 2021)
Posterior migration of sequestered disc of thoracic spine is an extremely rare case and can mimics spinal lesions like tumor, abcess, disc space infection or another space-occupying lesions. Our case is about 54 years old patient, female, who was admitted to the Neurosurgery Clinic due to severe paraparesis of the lower extremities with preserved sensitivity. MRI was very effective for the diagnosis of this rare pathological condition. Peripheral rim enhancement around the nonenhancing disc fragment is typical appearance on contrast MRI for disc fragment. Using the DWI sequence, we showed that there is no restriction of diffusion, which once again confirmed that it is not about an inflammation, not a tumor lesion. So, MRI as a diagnostic procedure offers opportunities to eliminate dilemmas regarding diagnosis in one fell swoop, which is necessary for the timely resolution of the patient’s condition.
Keywords: sequestered disc; thoracic spine; MRI; DWI sequence